Pengaruh Brand Image, Word of Mouth, Perceived Value Terhadap Repurchase Intention Pengguna Produk Skincare - Santiko, Ikfani Tri; Huda, Nurul (Journal of Business and Economics Research (JBE), 2025)
This study aims to analyze the influence of brand image, word of mouth (WOM), and perceived value on repurchase intention among Kahf skincare users in Jepara. The research employs a quantitative approach using a survey method and data analysis based on Partial Least Square (PLS). The sample consists of 96 respondents selected through purposive sampling. Data were collected using a five-point Likert scale questionnaire to measure the studied variables. The results show that the repurchase intention of Kahf skincare users in Jepara is significantly influenced by perceived value and word of mouth (WOM), as evidenced by the t-values of perceived value (4.618) and WOM (2.952), both greater than the t-table value of 1.66 with a significance level below 0.05. Meanwhile, brand image does not have a significant effect, as indicated by a t-value of 1.119 < 1.66 and a significance level of 0.264 > 0.05. These findings indicate that the higher the perceived value and positive WOM, the stronger the consumers’ repurchase intention, whereas brand image alone, without tangible perceived benefits, is insufficient to influence repurchase decisions.